MLL3/MLL4 are required for CBP/p300 binding on enhancers and super-enhancer formation in brown adipogenesis. Issue 11 (8th April 2017) - Lai, Binbin; Lee, Ji-Eun; Jang, Younghoon; Wang, Lifeng; Peng, Weiqun; Ge, Kai
Abstract: Histone H3K4me1/2 methyltransferases MLL3/MLL4 and H3K27 acetyltransferases CBP/p300 are major enhancer epigenomic writers. To understand how these epigenomic writers orchestrate enhancer landscapes in cell differentiation, we have profiled genomic binding of MLL4, CBP, lineage-determining transcription factors (EBF2, C/EBPβ, C/EBPα, PPARγ), coactivator MED1, RNA polymerase II, as well as epigenome (H3K4me1/2/3, H3K9me2, H3K27me3, H3K36me3, H3K27ac), transcriptome and chromatin opening during adipogenesis of immortalized preadipocytes derived from mouse brown adipose tissue (BAT). We show that MLL4 and CBP drive the dynamic enhancer epigenome, which correlates with the dynamic transcriptome. MLL3/MLL4 are required for CBP/p300 binding on enhancers activated during adipogenesis. Further, MLL4 and CBP identify super-enhancers (SEs) of adipogenesis and that MLL3/MLL4 are required for SE formation. Finally, in brown adipocytes differentiated in culture, MLL4 identifies primed SEs of genes fully activated in BAT such as Ucp1 . Comparison of MLL4-defined SEs in brown and white adipogenesis identifies brown-specific SE-associated genes that could be involved in BAT functions. These results establish MLL3/MLL4 and CBP/p300 as master enhancer epigenomic writers and suggest that enhancer-priming by MLL3/MLL4 followed by enhancer-activation by CBP/p300 sequentially shape dynamic enhancer landscapes during cell differentiation. Our data also provide a rich resource for understanding epigenomic regulation of brown adipogenesis.